In Pursuit of the Public Good: Access to Justice in the United States - Ruth Bader Ginsburg (Washington University Journal of Law & Policy, 2001)
The legal profession has among its practitioners brave men and women who strive to change that perception, jurists devoted to, and at work for, the public good—people who are the best of lawyers and judges, the most dedicated, the least selfish. Public service lawyering in the United States spans a wide range. In these remarks, I will endeavor to survey the territory, to identify both its inspiring and its dispiriting aspects, and to describe some promising recent developments. I will address primarily, but not exclusively, lawyering for persons who lack the wherewithal to pay fees.
Keywords: Legal assistance to the poor; Access to justice; Equal protection; Pro bono legal services